FRI0079 Rheumatoid factor as predictor of response to non TNF antagonist biologic therapies in rheumatoid arthritis: Systematic review and meta-analysis. (23rd January 2014) - Maneiro, J.R.; Salgado, E.; Carmona, L.; Gomez-Reino, J.J.
Abstract : Background: Currently, are searching for biomarkers to predict response to biological therapies and select patients with better response to each of them. Objectives: To identify if rheumatoid factor (RF) is predictor of response to rituximab (RTX), abatacept (ABT), and tocilizumab (TCZ) in rheumatoid arthritis (RA). Methods: Systematic review and meta-analysis of clinical trials and observational studies based on a sensitive search. Meta-regression was used to explore causes of heterogeneity. Unpublished data of clinical trials provided by the authors were also included. Results: The electronic search captured 3221 references and 422 meeting abstracts. By hand search, four additional articles were also identified. A total of 23 studies meet the purpose of the study and were included in the review. RF positivity at starting predicts better ACR20 [OR, 1.95 (1.24, 3.08)], ACR50 [OR, 5.38 (2.50, 11.60)] and EULAR response [OR, 3.52 (1.66, 7.45)] in 14 studies with RTX (Figure 1 ), and better ACR20 [OR, 1.51 (1.21, 1.90)] in 6 studies with TC. In 3 studies with ABT, no association was found between response and RF [OR 1.36 (0.97, 1.90)]. No asymmetries in the funnel plots or significant variables were found in the meta-regression. Conclusions: In RA, RF positivity predicts better response to RTX and TCZ but not to ABT. Disclosure of Interest: J. R. Maneiro: None Declared, E. Salgado: None Declared, L. Carmona Speakers Bureau: L.C. has received lecture fees from Abbott and Pfizer, J. J. Gomez-Reino Grant/Research support from: JJ.G-R has received research grants from Roche and Schering-Plough, Consultant for: JJ.G-R is on the Advisory Boards of BMS, Pfizer, Roche, Schering-Plough and UCB SA, Speakers Bureau: JJ.G-R has received lecture fees from, BMS, Roche, Schering-Plough and Wyeth